O velho no ciberespaço: sociabilização nos blogs de cidadãos acima de 60 anos - Azevedo, Celina Dias (2009)
The computer, allied with the Internet-based communication process, is the center of a transformation that involves and intermediates actions of communication, economy, work, and access to information in the globalized society. This study reflects on how this technology started to mediate our daily life, configuring the social relations. Our aim was to investigate how the elderly use the new communication technologies to experiment new social spaces. The theorists whose ideas supported this work are Manuel Castells and Pierre Levy, who understand cyberspace as an important territory for communication and social interaction. The focus selected for the research was the Weblog, a kind of website that has the characteristic of strong interactivity. Using search sites on the Internet we looked for examples of blogs that had in the profile/blogger identification (over 60 years of age) posts with keywords (old person; elderly; maturity; aging; third age), indication of blogs, blogs of elderly people disseminated in the media and others, with the same characteristics, found in the blogroll of the bloggers who are the subjects of this study. The sample is composed of seven blogs, of which four were monitored from December 2007 to September 2008. The examples do not intend to be a statistic parameter; rather, they indicate a tendency. Three criteria were defined to choose the blogs that would be analyzed, by means of non-participatory research: the blog is/has remained on the air or has been updated for at least six months; the blogger/author is 60 years old or more and the age is informed in his blog profile; and blog of any category. The blogs were classified as Individual expression blogs, created by a single blogger; Collective or group expression blogs, created by more than one blogger; and Mixed, created by one single blogger which publishes posts whose authorship is not the blogger s. Analyzing the meaning of the expressions used by the elderly in cyberspace, we observed that there are examples of action in the cyberspace that gives visibility to the elderly and to aging; the elderly person uses the blog as a socialization and individual expression space; the elderly manifest their autonomy when they create an independent socialization space; and the utilization of the blog creates opportunities to access other environments on the net. We noticed an extension of the use of the blog beyond the resource of virtual diary , configuring a multiple and complex social space of individual expression, but also of learning and informative, cooperative and literary convergence